Pitt on a Pedestal: Sculpture and Slavery in Late-Eighteenth-Century Charleston - Wendy Bellion (European Journal of American Studies)
On July 5, 1770, South Carolina raised its first public sculpture. Representing the English statesman William Pitt the Elder in the mode of a classical orator, the marble statue stood on a pedestal at the intersection of Meeting and Broad Streets, in Charleston’s historic Civic Square. This essay reconstructs the significance of its location and its competing meanings within the colonial slave city. It examines how the statue functioned to reflect the racial politics of elite Charlestonians while illuminating the cultures of surveillance, discipline, and display that linked black and white bodies. At the symbolic center of the urban landscape, the figure of Pitt exposed the implicated nature of neoclassical sculpture and transatlantic slavery.